2009
DOI: 10.1071/rd09039
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications and related mRNA expression during bovine oocyte in vitro maturation

Abstract: The present study investigated the global pattern of two histone modifications and methylation of DNA during in vitro maturation of bovine oocytes retrieved from follicles of two different sizes (<2 mm and 2-8 mm). The methylation status of histone H3 at position lysine K9 (H3K9 me2), the acetylation status of histone H4 at position lysine K12 (H4K12ac) and the methylation of DNA were assessed by immunocytochemistry. In parallel, the relative abundance of mRNAs coding for proteins specifically involved in repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 45 publications
2
56
2
Order By: Relevance
“…35,36 So far, the methylation status of different lysine and arginine residues on histone H3 and H4 has been examined in mouse, porcine, sheep, bovine and human oocytes. 20,23,[37][38][39][40][41][42] Immunostaining coupled with confocal microscopy has revealed that, in contrast to acetylation and phosphorylation, histone methylation appears to be relatively stable during oocyte maturation, as shown in Table 3. Methylated histones are basically colocalized with chromosomes in mammalian oocytes, whereas H3K79me3 was observed in the pericentromeric heterochromatin regions of meiotic chromosomes.…”
Section: Regulation Of Histone Modifications In Mammalian Oocytementioning
confidence: 99%
“…35,36 So far, the methylation status of different lysine and arginine residues on histone H3 and H4 has been examined in mouse, porcine, sheep, bovine and human oocytes. 20,23,[37][38][39][40][41][42] Immunostaining coupled with confocal microscopy has revealed that, in contrast to acetylation and phosphorylation, histone methylation appears to be relatively stable during oocyte maturation, as shown in Table 3. Methylated histones are basically colocalized with chromosomes in mammalian oocytes, whereas H3K79me3 was observed in the pericentromeric heterochromatin regions of meiotic chromosomes.…”
Section: Regulation Of Histone Modifications In Mammalian Oocytementioning
confidence: 99%
“…In our opinion the intrinsic features of oocytes including elements related to maternal nutrition, can be analyzed only directly after COC recovery from ovarian follicles. It is well documented that in vitro maturation significantly affects the profile and quality (e.g., adenylation status) of transcripts in mammalian oocytes (BreviniGandolfi et al, 1999;Racedo et al, 2009). Thus, by analyzing the transcripts of in vitro-matured oocytes it would not be possible to distinguish between changes induced by maternal nutrition and by the IVM process itself.…”
Section: Transcript Content Of Genes Related To Oocyte Qualitymentioning
confidence: 99%
“…G9a interacts with Dnmt1 and both Dnmt3s, thereby stimulating their activities during prenatal testis development (Esteve et al, 2006) and aiding in the silencing of selected target sequences including Oct4 (Fig. 2) (Feldman et al, 2006), retrotransposons and imprinting control regions (ICRs) (Mann et al, 2000;Racedo et al, 2009). Two additional SET domain-containing histone methyltransferases, Ezh1 (enhancer of zeste homologue) and Setd1b (SET domain, bifurcated 1), are also up-regulated in progametogonia and contribute to sequence specific H3K9 and H3K27 methylation (Lefevre and Mann, 2008).…”
Section: Resetting the Somatic Genome In Primordial Germ Cellsmentioning
confidence: 99%